2017
DOI: 10.1007/s00417-017-3772-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TLR4 alleviates the inflammation and apoptosis of retinal ganglion cells in high glucose

Abstract: Our results demonstrated that TLR4 plays a critical role in the inflammation and apoptosis of RGCs induced by high glucose. TLR4 might become a novel potential pharmacological target for preventing the progression of DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 52 publications
3
27
0
4
Order By: Relevance
“…Studies revealed that TLR4 is involved in the activity of late endothelial progenitor cells (32) and was upregulated in the retina of DR rats and in HRECs cultured in HG (33). The TLR4/NF-κB signaling pathway was activated in retinal ganglion cells under high glucose and TLR4 inhibition suppressed HG-induced apoptosis (34). Consist with previous studies, the activation of TLR4/NF-κB pathway was observed with the treatment of HG in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…Studies revealed that TLR4 is involved in the activity of late endothelial progenitor cells (32) and was upregulated in the retina of DR rats and in HRECs cultured in HG (33). The TLR4/NF-κB signaling pathway was activated in retinal ganglion cells under high glucose and TLR4 inhibition suppressed HG-induced apoptosis (34). Consist with previous studies, the activation of TLR4/NF-κB pathway was observed with the treatment of HG in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…Toll-like receptor 4 (TLR4) is a type of pattern recognition receptor, and is involved in innate and adaptive immunity by producing pro-inflammation cytokines, chemokines and apoptosis [9] . Studies have reported that TLR4 in the central nervous system (CNS) involved in memory, learning impairment [10] and cognitive decline [11].…”
Section: Introductionmentioning
confidence: 99%
“…Retinal ganglion cells (RGCs) are output neurons which relay visual signals from the retina to the brain visual centers. Mice RGCs treated with 5 mM fructose upregulated NLRP1 expression after 24 h [109], while rat RGCs stimulated with 20 mM glucose for 48 h upregulated NLRP3 expression [127]. Inhibition of TLR4 using TAK-242 was found to attenuate NLRP3 and IL-1β production in the rat RGCs [127].…”
Section: Nlrs In Diabetic Retinopathymentioning
confidence: 95%
“…Mice RGCs treated with 5 mM fructose upregulated NLRP1 expression after 24 h [109], while rat RGCs stimulated with 20 mM glucose for 48 h upregulated NLRP3 expression [127]. Inhibition of TLR4 using TAK-242 was found to attenuate NLRP3 and IL-1β production in the rat RGCs [127]. Retinal microvascular endothelial cells form the crucial inner BRB that shields the inner retina from circulatory insult.…”
Section: Nlrs In Diabetic Retinopathymentioning
confidence: 98%